Exploring the sonodynamic effects of bacteriochlorophyll a - Jia, Lanqi; Wang, Longhao; Song, Yiqiong; Pang, Xin; Zhao, Jie (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: The purpose of this study was to investigate whether bacteriochlorophyll a (BCA) could be used as a potential diagnostic factor in near-infrared fluorescence (NIRF) imaging and in mediating sonodynamic antitumor effect. Methods: The UV spectrum and fluorescence spectra of bacteriochlorophyll a were measured. The IVIS Lumina imaging system was used to observe the fluorescence imaging of bacteriochlorophyll a. 9,10-Dimethylanthracene (DMA) reagent was used as a singlet oxygen sensor to detect singlet oxygen produced by bacteriochlorophyll a. LLC cells of mouse lung adenocarcinoma were selected as experimental subjects. Flow cytometry was used to detect the optimal uptake time of bacteriochlorophyll a in LLC cells. A laser confocal microscope was used to observe the binding of bacteriochlorophyll a to cells. The cell survival rate of each experimental group was detected by the CCK-8 method to detect the cytotoxicity of bacteriochlorophyll a. The effect of BCA-mediated sonodynamic therapy (SDT) on tumor cells was detected by the calcein acetoxymethyl ester/propidium iodide (CAM/PI) double staining method. 2,7-Dichlorodihydrofluorescein-diacetate (DCFH-DA) was used as the staining agent to evaluate and analyze intracellular reactive oxygen species (ROS) levels by fluorescence microscopy and flow cytometry (FCM). A confocal laser scanning microscope (CLSM) was used to observe the localization in the organelles of bacteriochlorophyll a. The IVIS Lumina imaging system was used to observe the fluorescence imaging of BCA in vitro. Results: Bacteriochlorophyll a-mediated SDT significantly increased cytotoxicity to LLC cells compared to other treatments, such as ultrasound (US) only, bacteriochlorophyll a only, and sham therapy. The CLSM observed bacteriochlorophyll a aggregation around the cell membrane and cytoplasm. FCM analysis and fluorescence microscopy showed that bacteriochlorophyll a-mediated SDT in LLC cells significantly inhibited cell growth and caused an obvious increase in intracellular ROS levels, and its fluorescence imaging function suggests that it can be a potential diagnostic factor. Conclusion: The results showed that bacteriochlorophyll a possesses good sonosensitivity and fluorescence imaging function. It can be effectively internalized in LLC cells, and bacteriochlorophyll a-mediated SDT is associated with ROS generation. This suggests that bacteriochlorophyll a can be used as a new type of sound sensitizer, and the bacteriochlorophyll a-mediated sonodynamic effect may be a potential treatment for lung cancer.